Hyaluronic Acid-Based Hybrid Nanoparticles as Promising Carriers for the Intranasal Administration of Dimethyl Fumarate - Serri C; Piccioni M; Guarino V; Santonicola P; Cruz-Maya I; Crispi S; Di Cagno MP; Ferraro L; Dalpiaz A; Botti G; Giunchedi P; Rassu G; et al. (International Journal of Nanomedicine)
Carla Serri,1 Miriam Piccioni,2 Vincenzo Guarino,3 Pamela Santonicola,2 Iriczalli Cruz-Maya,3 Stefania Crispi,2 Massimiliano Pio Di Cagno,4 Luca Ferraro,5 Alessandro Dalpiaz,6 Giada Botti,6 Paolo Giunchedi,1 Giovanna Rassu,1 Elisabetta Gavini1 1Department of Medicine, Surgery and Pharmacy, University of Sassari, Sassari, Italy; 2Institute of Biosciences and Bio-Resources, National Research Council (CNR-IBBR), Naples, Italy; 3Institute of Polymers, Composites and Biomaterials, National Research Council of Italy, Naples, Italy; 4Department of Pharmacy, University of Oslo, Oslo, Norway; 5Department of Life Sciences and Biotechnology, University of Ferrara and LTTA Center, Ferrara, Italy; 6Department of Chemical, Pharmaceutical and Agricultural Sciences, University of Ferrara, Ferrara, ItalyCorrespondence: Giovanna Rassu, Department of Medicine, Surgery and Pharmacy, University of Sassari, Sassari, Italy, Email grassu@uniss.itPurpose: Dimethyl fumarate (DMF), the first-line oral therapy for relapsing-remitting multiple sclerosis, is rapidly metabolized into monomethyl fumarate. The DMF oral administration provokes gastrointestinal discomfort causing treatment withdrawal. The present study aimed to develop an innovative formulation for DMF nasal administration. Lipid-polymer hybrid nanoparticles (LPNs) were developed to improve DMF stability, limiting gastrointestinal side effects and increasing brain bioavailability by nose-to-brain targeting application.Methods: DMF-loaded and unloaded LPNs with or without hyaluronic acid (HA) were prepared using the nanoprecipitation via magnetic/mechanical stirring technique. Particle morphology and surface properties were evaluated; drug content, viscosity, and mucoadhesion were determined. Physico-chemical stability of LPNs and DMF in the LPNs was also explored. In vitro DMF permeation experiments were performed utilizing the PermeaPad®. The cytotoxicity and cellular uptake studies were performed using RPMI 2650 and SK-N-BE2 cell lines. DMF nose-to–brain delivery was evaluated by intranasally administering DMF-loaded LPNs to rats.Results: LPNs with average sizes of 120– 250 nm and a negative zeta potential − 17.3 to − 43 mV were obtained, primarily influenced by the presence of HA. HA assured drug stability up to 60 days and promoting the in vitro permeation of DMF compared to the free-DMF. HA greatly improved the viscosity and mucoadhesive properties. LPNs with and without HA did not exhibit any cytotoxicity and showed a rapid cell uptake starting from 15 min to 2 h with a best internalization after 1 h of treatment in both epithelial and neuronal cell lines. Nasal administration of DMF-loaded LPNs allowed to quantify up to about 12 μg/mL of DMF in the rat cerebrospinal fluid.Conclusion: The results highlight the role of HA in improving LPNs properties and performance as carrier of DMF for nasal administration. In particular, LPNs appear able to enter neurons and monolayers of epithelial cells, allowing to promote the nose-to-brain DMF delivery. Keywords: hyaluronic acid, lipid and polymeric nanoparticles, nasal administration, nose-to-brain delivery, dimethyl fumarate, cell uptake